Knowledge and awareness on breast cancer among midwives and auxiliary midwives from three townships in Lower Myanmar - Oo, Khin May; Shwe, San; Win, Le Le; Khin, Myo; Min, Aung Myo; Htut, Ye; Win, Htain (International Journal Of Community Medicine And Public Health, 2022)
Background: In Myanmar, more than seventy percent of the population reside in rural areas and as the midwives (MW) and auxiliary midwives (AMW) are the basic health care workers who provide crucial health information to the rural women, their knowledge and awareness on breast cancer needs to be explored. Methods: A cross-sectional descriptive study was carried out to assess the perceived knowledge and awareness of MWs and AMWs regarding the early signs and symptoms, risk factors, and screening of breast cancer. Results: A total of 203 respondents (including 154 MWs and 49 AMWs) participated in the study. The mean age of the participants was 20.27±3.6 years and the majority (96%) was single. The majority of respondents (94%) had heard of breast cancer and breast cancer screening. AMWs had a significantly lower knowledge on risk factors such as: family history (68% versus 19%); nulliparity (62% versus 43%); change in shape of breast (47% versus 25%); dimpling (44.3% versus 18.45%); lumps in axilla (42% versus 21%); use of oral contraceptive pills (34% versus 8%) than the MWs. Conclusions: More knowledge on breast cancer and breast cancer screening need be imparted to the MWs and AMWs to be able to convey knowledge and information of breast cancer to the women residing in rural areas.